Police-Public Contact Survey, 2008 ([Verlag nicht ermittelbar], 2011)
The Police-Public Contact Survey (PPCS) provides detailed information on the nature and characteristics of face-to-face contacts between police and the public, including the reason for and outcome of the contact. The PPCS interviews a nationally representative sample of United States residents aged 16 years or older as a supplement to the National Crime Victimization Survey. To date, the PPCS has been conducted five times by the Bureau of Justice Statistics (BJS): The first survey -- described in the BJS publication Police Use of Force: Collection of National Data (NCJ 165040) -- documented levels of contacts with police during 1996. The second survey -- described in Contacts between Police and the Public: Findings from the 1999 National Survey (NCJ 184957) -- recorded police-citizen contacts in 1999. These data are archived as POLICE-PUBLIC CONTACT SURVEY, 1999: [UNITED STATES] (ICPSR 3151). The third survey -- described in Contacts between Police and the Public: Findings from the 2002 National Survey (NCJ 207845) -- covered interactions between police and the public in 2002. These data are archived as POLICE-PUBLIC CONTACT SURVEY, 2002: [UNITED STATES] (ICPSR 4273). The fourth survey -- described in the BJS publication, Contacts between Police and the Public, 2005 (NCJ 215243) -- covered interactions between police and the public in 2005. These data are archived as POLICE-PUBLIC CONTACT SURVEY, 2005: [UNITED STATES] (ICPSR 20020). The fifth survey -- described in the BJS publication, Contacts between Police and the Public, 2008 (NCJ 234599) -- covered interactions between police and the public in 2008. These data are archived as POLICE-PUBLIC CONTACT SURVEY, 2008 (ICPSR 32022).